Penyuluhan Hukum Terkait Judi Online Bagi Generasi Milenial (Studi di Kota Banda Aceh) - Hadi Iskandar; Budi Bahreisy; Ferdy Saputra; Romi Asmara; Yusrizal Yusrizal; Hidayat Hidayat (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2022)
The development of technology and information in the form of the internet has grown rapidly. Not only for the elderly, but also for young people who use it, the increasingly easy use of the internet has been misused for gambling games. Initially people access online games, then out of curiosity and curiosity, people follow online gambling. Online games as an unreal virtual space make users free to do things that are prohibited in life, both in religious norms and prohibited by law, such as online gambling. Based on this background, the formulation of the problem from this legal counseling is how the criteria for online gambling criminal acts and how to sanction online gambling crimes in the perspective of Islamic law and national law. This legal counseling activity is carried out using lecture and discussion methods. Participants were given motivation and understanding about understanding online gambling in the perspective of Islamic criminal law and national criminal law. In addition, participants were given material on the importance of understanding the criteria for acts of online gambling and the sanctions of online gambling crimes. The objectives of the service to the millennial generation in Banda Aceh City are to: 1). Provide knowledge about the criteria for online gambling crimes and 2). Providing understanding to the millennial generation about online gambling criminal sanctions in the perspective of Islamic Law and National Law. this is also part of capturing problems that occur in society.